2019
DOI: 10.1027/1015-5759/a000394
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of the Interpersonal Affect Improvement Strategies Questionnaire

Abstract: Abstract. This research outlines the development and validation of a new self-report measure to assess the tendency to use different interpersonal affect improvement strategies within the normal adult population (Interpersonal Affect Improvement Strategies Questionnaire, IAISQ). The scale is based on the interpersonal affect classification (IAC; Niven, Totterdell, & Holman, 2009 ) and accurately distinguishes between the two primary means suggested in that model: positive engagement and acceptance. Through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 35 publications
2
15
0
Order By: Relevance
“…Improving others' emotions can be achieved in two main ways: Either dealing with the situation/emotion directly (positive engagement) or by focusing on the person experiencing the emotion without engaging with the emotion directly (acceptance, see table 1). This classi cation has been validated by López-Pérez, Morillo (5) and will therefore be used in this protocol and study.…”
Section: Interpersonal Emotion Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Improving others' emotions can be achieved in two main ways: Either dealing with the situation/emotion directly (positive engagement) or by focusing on the person experiencing the emotion without engaging with the emotion directly (acceptance, see table 1). This classi cation has been validated by López-Pérez, Morillo (5) and will therefore be used in this protocol and study.…”
Section: Interpersonal Emotion Regulationmentioning
confidence: 99%
“…To our knowledge, López-Pérez, Morillo (5) are the only ones who tested sex differences concerning speci c iER strategies de ned by classi cations. They found that women tend to use positive engagement more often than men, which gives preliminary evidence that women engage in the social affective component of iER strategies more than men.…”
Section: Interpersonal Emotion Regulationmentioning
confidence: 99%
“…These dimensions focus on the individual’s ability to promote positive feelings in others, but not negative feelings or their intentionality, overlooking the fact that both types of emotions coexist in human relationships. Similarly, the Interpersonal Affect Improvement Strategies Questionnaire (IAISQ), developed by López-Pérez et al [ 21 ], focuses on the intention to enhance other people’s emotions, but not on the desire to make the other person feel bad. It presented adequate construct validity evidence and acceptable reliability.…”
Section: Introductionmentioning
confidence: 99%
“…Improving others’ emotions can be achieved in two main ways: either dealing with the situation/emotion directly (positive engagement) or by focusing on the person experiencing the emotion without engaging with the emotion directly (acceptance, see Table 1 ). This classification has been validated by López-Pérez, Morillo [ 5 ] and will therefore be used in this protocol and study.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, López-Pérez, Morillo [ 5 ] are the only ones who tested sex differences concerning specific iER strategies defined by classifications. They found that women tend to use positive engagement more often than men, which gives preliminary evidence that women engage in the social affective component of iER strategies more than men.…”
Section: Introductionmentioning
confidence: 99%